Magnetically separable h-Fe3O4@phosphate/polydopamine nanospheres for U(VI) removal from wastewater and soil. Issue 6 (December 2022) - Zhang, Jianfeng; Wang, De; Cao, Ruya; Sun, Fuwei; Li, Jiaxing
Abstract: In this work, a magnetic h-Fe3 O4 @phos-PDA nanocomposite composed of ferroferric oxide hollow nanosphere and phosphate-modified polydopamine shell was successfully prepared by a facile one-step method. The h-Fe3 O4 @phos-PDA nanocomposite has excellent adsorption properties for U (VI) under the action of phosphate and amine functional groups. The maximum adsorption capacity of h-Fe3 O4 @phos-PDA for U(VI) in pH= 5 aqueous solution reached 526.35 mg/g at 298 K, and the adsorption process conformed to the Langmuir isotherm model. The analysis of kinetic adsorption data educed that the adsorption process followed the pseudo-second-order model and reached equilibrium in just 16 min. XPS analysis indicated that phosphate and amine functional groups play a vital role in the complexation between the phos-PDA shell and U (VI). In addition, actual soil remediation experiments indicated that the h-Fe3 O4 @phos-PDA nanocomposite could reduce the radiation intensity of α-ray in uranium-contaminated soil by about 82.3%, demonstrating its great engineering application potential. Graphical Abstract: Magnetically separable nanocomposite with hollow Fe3 O4 core and phosphate/polydopamine hybrid shell was synthesized by in situ redox polymerization, which exhibited excellent adsorption properties for U (VI) due to the abundant phosphate and amine functional groups. ga1 Highlights: The h-Fe3 O4 @phos-PDA has excellent adsorption performance for U(VI). The maximum capacity of U(VI) adsorbed by h-Fe3 O4 @phos-PDA reached 526.35 mg/g. The synthesis method of h-Fe3 O4 @phos-PDA is simple and easy to operate. The h-Fe3 O4 @phos-PDA can reduce the radiation intensity of uranium-bearing soil.